Adorno's gamble : harnessing German ideology - Immanen, Mikko, 1982- (Signale (Ithaca, N.Y.), 2025)
"The book reinterprets the thought of Theodor W. Adorno, the leading light of the Frankfurt School and one of the most influential leftist intellectuals of the twentieth century, by arguing that his worries over the frailty of reason and democracy were inspired by radical conservative thinkers of Weimar Germany"--